Analisa faktor-faktor yang mempengaruhi intention masyarakat menggunakan platform telehealth pasca pandemi Covid-19 - Sarah Geltri Harahap; Ellynia Ellynia; Andrianto Widjaja (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Telehealth is a form of health service innovation used during the Covid-19 pandemic where users can use this technology without having to go to the hospital for their health. The development of health services towards digitization has begun to develop in health services in Indonesia. Hospitals in Indonesia, especially in Jabodetabek, have adopted many telehealth services.Purpose: To analyze the factors that influence people's intention to use telehealth so that they can develop telehealth innovations by looking at the dimensions of technology and users.Method: The study was conducted using a quantitative approach with a cross-sectional design using primary data. The analysis used was univariate, chi-square test, and multiple linear regression test.Results: From a total of 109 respondents it was found that the factors that most influenced community interest from the technology dimension were social support (p=0.005) and facilities and infrastructure (p=0.005) where the technology dimension obtained an R square of 0.917 while on the user dimension, the most influencing community intentions are perceived usefulness (p = 0.005) and perceived convenience (p = 0.005), where the user dimension factor has an R square of 0.874.Conclusion: There is a relationship between perceived usefulness, perceived ease of use, and intention to use the community in using the telehealth platform in the community of Jabodetabek. The factors of perceived ease to use, perceived usefulness, social influence, and facilitating conditions are the factors that most influence people's intention to use telehealth in Jabodetabek.Suggestion: The technology dimension factor and the user dimension are things that must be considered for the future development of telehealth technology so that patients are more loyal to reusing telehealth applications during the post-Covid-19 pandemic health digitalization.Keywords: Community Intentions; Telehealth; Pandemic; Covid-19.Pendahuluan: Telehealth merupakan bentuk inovasi pelayanan kesehatan yang telah dimanfaatkan di masa pandemi Covid-19 dimana pengguna dapat menggunakan teknologi tersebut tanpa berkunjung ke rumah sakit untuk kesehatannya. Perkembangan pelayanan kesehatan ke arah digitalisasi sudah mulai berkembang di pelayanan kesehatan di Indonesia. Rumah sakit di Indonesia khususnya di Jabodetabek sudah banyak mengadopsi layanan telehealth.Tujuan: Untuk menganalisa faktor- faktor yang mempengaruhi intention masyarakat dalam menggunakan telehealth sehingga dapat mengembangkan inovasi telehealth dengan melihat dimensi technology dan user dimension.Metode: Penelitian dilakukan dengan pendekatan kuantitatif dengan desain cross sectional menggunakan data primer. Analisis yang digunakan adalah univariate, uji chi square, uji regresi linear berganda.Hasil: Dari total 109 responden ditemukan bahwa faktor yang paling mempengaruhi intention masyarakat dari dimensi teknologi adalah dukungan social (p= 0.005) dan factor fasilitas sarana dan prasarana dengan (p=0.005) dimana dimensi teknologi diperoleh R square sebesar 0.917 sedangkan pada dimensi user, yang paling mempengaruhi intention masyarakat adalah persepsi kemanfaatan (p =0.005) dan persepsi kemudahan (p=0.005), dimana faktor user dimension memiliki R square 0.874.Simpulan: Terdapat hubungan perceived usefulness, perceived ease of use terhadap intention to use pada masyarakat dalam menggunakan platform telehealth pada masyarakat di Jabodetabek. Faktor perceived ease to use, perceived usefulness, social influence, dan facilitating condition adalah faktor yang paling mempengaruhi intention masyarakat dalam menggunakan telehealth di Jabodetabek.Saran: Faktor dimensi teknologi dan dimensi pengguna merupakan hal yang harus dipertimbangkan untuk mengembangkan teknologi telehealth di masa yang akan datang sehingga pasien semakin loyal menggunakan kembali aplikasi telehealth di masa digitalisasi kesehatan pasca pandemic Covid-19